Reactions to UV damage in the model archaeon Sulfolobus solfataricus. (20th January 2009) - Fröls, Sabrina; White, Malcolm F.; Schleper, Christa
Abstract : Mechanisms involved in DNA repair and genome maintenance are essential for all organisms on Earth and have been studied intensively in bacteria and eukaryotes. Their analysis in extremely thermophilic archaea offers the opportunity to discover strategies for maintaining genome integrity of the relatively little explored third domain of life, thereby shedding light on the diversity and evolution of these central and important systems. These studies might also reveal special adaptations that are essential for life at high temperature. A number of investigations of the hyperthermophilic and acidophilic crenarchaeote Sulfolobus solfataricus have been performed in recent years. Mostly, the reactions to DNA damage caused by UV light have been analysed. Whole-genome transcriptomics have demonstrated that a UV-specific response in S. solfataricus does not involve the transcriptional induction of DNA-repair genes and it is therefore different from the well-known SOS response in bacteria. Nevertheless, the UV response in S. solfataricus is impressively complex and involves many different levels of action, some of which have been elucidated and shed light on novel strategies for DNA repair, while others involve proteins of unknown function whose actions in the cell remain to be elucidated. The present review summarizes and discusses recent investigations on the UV response of S. solfataricus on both the molecular biological and the cellular levels.